Robust Effective‐Medium Characteristics of Bianisotropic Reflective Metasurfaces based on Field‐Circuit Combined Analysis. Issue 2 (14th January 2021) - Han, Feng‐Yuan; Yin, Li‐Zheng; Du, Chao‐Hai; Liu, Pu‐Kun
Abstract: As a bridge linking propagating waves and surface waves, reflective metasurfaces (with metal cladding at the bottom) play a significant role in the field of beam steering. The feasibility and flexibility to control electromagnetic waves by reflective metasurfaces depend on the recognition of their physical properties by researchers. As for bianisotropic reflective metasurfaces, however, the effective‐medium characteristics cannot be appropriately described by conventional methods, which entail both transmission and reflection coefficients. Here, a robust method based on simplex S ‐parameters is proposed to retrieve constitutive effective parameters (CEPs) for bianisotropic reflective metasurfaces. By illuminating the transverse electric‐polarization plane waves on a split‐ring unit cell normally and obliquely, the CEPs can be calculated with only S 11 parameters. To demonstrate the effectiveness of the retrieval results, an analysis of small incident angles is employed to examine the consistency of both the x ‐ and y ‐directions effective impedance and determine the accurate range of the incident angles. Moreover, the sensitivity of the retrieval results to S ‐parameters is also sufficiently discussed. This method is beneficial for the applications of one‐side complex materials, e.g., dual‐function reflective metasurfaces, multichannel reflectors, excitation of spoof space plasmon polaritons, and ground‐penetrating‐radar applications. Abstract : To precisely describe the effective‐parameter characteristics for bianisotropic reflective metasurfaces, a robust extraction theory based on simplex S ‐parameters in the field‐circuit combined analysis is proposed to retrieve both the x ‐ and y ‐directions effective constitutive parameters. The effectiveness of the proposed method is demonstrated theoretically and numerically. This method is beneficial for the design of dual‐function reflective metasurfaces, multichannel reflectors, etc.